The Biology of Ewing Sarcoma. (3rd January 2013) - Ross, Keir A.; Smyth, Niall A.; Murawski, Christopher D.; Kennedy, John G.
Abstract : Objective . The goal of this study was to review the current literature on the biology of Ewing's sarcoma, including current treatments and the means by which an understanding of biological mechanisms could impact future treatments. Methods . A search of PubMed and The Cochrane Collaboration was performed. Both preclinical and clinical evidence was considered, but specific case reports were not. Primary research articles and reviews were analyzed with an emphasis on recent publications. Results . Ewing sarcoma is associated with specific chromosomal translocations and the resulting transcripts/proteins. Knowledge of the biology of Ewing sarcoma has been growing but has yet to significantly impact or produce new treatments. Localized cases have seen improvements in survival rates, but the same cannot be said of metastatic and recurrent cases. Standard surgical, radiation, and chemotherapy treatments are reaching their efficacy limits. Conclusion . Improving prognosis likely lies in advancing biomarkers and early diagnosis, determining a cell(s) of origin, and developing effective molecular therapeutics and antiangiogenic agents. Preclinical evidence suggests the utility of molecular therapies for Ewing sarcoma. Early clinical results also reveal potential for novel treatments but require further development and evaluation before widespread use can be advocated.